Notch sensitivity in nanoscale metallic glass specimens: Insights from continuum simulations. (January 2016) - Singh, I.; Narasimhan, R.
Abstract: Recent experiments have shown that nano-sized metallic glass (MG) specimens subjected to tensile loading exhibit increased ductility and work hardening. Failure occurs by necking as opposed to shear banding which is seen in bulk samples. Also, the necking is generally observed at shallow notches present on the specimen surface. In this work, continuum finite element analysis of tensile loading of nano-sized notched MG specimens is conducted using a thermodynamically consistent non-local plasticity model to clearly understand the deformation behavior from a mechanics perspective. It is found that plastic zone size in front of the notch attains a saturation level at the stage when a dominant shear band forms extending across the specimen. This size scales with an intrinsic material length associated with the interaction stress between flow defects. A transition in deformation behavior from quasi-brittle to ductile becomes possible when this critical plastic zone size is larger than the uncracked ligament length. These observations corroborate with atomistic simulations and experimental results. Abstract : Highlights: Tensile response of nano-sized notched metallic glass sample is analyzed. Average stress in ligament at peak load is close to tensile yield strength. Plastic yielding ahead of the notch tip saturates when a dominant shear band forms. Brittle to ductile transition occurs for small ligament to material length ratio. Results corroborate with atomistic simulations and experimental observations.